Centro de educação básica e profissional para jovens e adultos em vulnerabilidade social - Câmara, João Vitor dos Reis (Brasil, 2022)
In this work, theoretical foundations will be presented that help the understanding as well as data that emphasize the importance of the built object for the community, from the perspective of the groups most affected by the crisis and pandemic in the last 2 and a half years, in addition to the conceptual and project proposal. with its proper guidelines and program of needs.